Analysis of Understanding The Use of Javanese Language "Krama Inggil" of Preservice Teachers in Primary Teacher Education Programs - Ngatman Ngatman (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
This study aims to analyze the understanding the use of Javanese language "krama inggil" of preservice teachers in primary teacher education programs. This research is a descriptive study of 84 research subjects. The instruments used were description test sheets, questionnaire sheets, and interview sheets. The data analysis technique uses descriptive qualitative. The results of the analysis show that: 1) The average value of understanding the use of Javanese language "krama inggil" was 78; 2) students who are able to communicate using good manners and apply in daily life as much as 38.61%; 3) Some of the difficulties factors of students using Javanese language "krama inggil" include not being accustomed from childhood, parents do not teach Javanese language "krama inggil", preferring to use Indonesian, lacking the motivation to use Javanese language "krama inggil" because it is difficult to pronounce.